Impact of the Insolvency and Bankruptcy Code on Non-Performing Assets - Jeevan Nagarkar, Samira Rawoof (International Journal of Modern Agriculture, 2020)
Purpose: This research paper aims to assess the implementation of the IBC and its impact on NPAs and the Indian banking system as a whole. Approach/Methodology: The research adopted the approach of content analysis, where quality articles, excerpts, news articles and research papers have been thoroughly studied and documented. Findings: The two prime findings are, firstly the IBC has the power to bring about sweeping changes in insolvency proceedings and resolution, and thisshould indirectly encourage healthy business functioning in India. Secondly, banks will be required to couple the effect of the IBC by following adequate corporate governance and lending practises to ensure such challenges, such as NPAs do not crop up again. Research: The research methodology adopted is qualitative and secondary in nature. Based on secondary research obtained interpretations, opinions and conclusions have been drawn. Value: The paper will aid further research and studies on topics of corporate governance and lending practises of banks.